The Performance of Acid Lime (Citrus aurantifolia Swingle) Cultivars in Mass Propagation Using Hard Wood Cuttings under Shade Net - Prakasha, D. P.; Malkar, Ashish; Kulapati, H.; Anand, N. (International Journal of Economic Plants, 2025)
The experiment was carried out during (June–Sep) during (June–September) 2019–2020 and 2020–2021, respectively at College of Horticulture, UHS, Bagalkot, Karnataka, India to evaluate the mass propagation performance of different cultivars of acid lime (Citrus aurantifolia Swingle) viz. Kagzi lime, Sai Sharbati, Balaji, Vikram and Pramalini using a methodology involving hardwood cuttings, treatment with 500 ppm IBA, cocopeat as growing media under shade net condition. The statistical design employed was Completely Randomised Design (CRD). The results were significantly affected in all parameters. The lowest number of days taken for sprout initiation was recorded in cv. Balaji (8.5 days) and highest was in cv. Vikram (13.4 days), respectively. The highest and lowest sprout percent was recorded in cv.Vikram (91.66%) and cv. Kagzi lime (48.61%). Shoot length was increased up to 90 days and the highest shoot length was in cv. Vikram (13.10 cm) and lowest was in cv. Balaji (7.19 cm). The highest and lowest fresh and dry weight was recorded in cv. Saisarbati (8.54 g and 6.29 g) and cv.Pramalini (7.19 g and 3.67 g), respectively. The highest and lowest number of primary roots was recorded in cv. Vikram (4.2) and Sai sarbati (2.6), highest and lowest average root length was recorded in cv.Vikram (18.70 cm) and Kagzi lime (12.26 cm), respectively, highest and lowest rooting percent was recorded in cv. Vikram (88.88%) and Kagzi lime (45.83), respectively at 90 DAP. There was considerable variation in responses which genotype dependent. The results are helpful in future root stock studies as well as mass multiplication of planting material on commercial scale.